Manajemen Kinerja Berbasis Budaya Keagamaan dalam Meningkatkan Profesionalisme Guru di SMP Islam al-Azhar 5 Cirebon - Kurniawan, Asep (Holistik: Journal for Islamic Social Sciences, 2019)
The purpose of this study is to reveal in depth the ability of principals to improve teacher professionalism through performance management based on religious culture in al-Azhar 5 Islamic Middle School, Cirebon City. This research is a qualitative descriptive case study. Data collection instruments adopted by in-depth observation, in-depth interviews, and documentation. Stages of data analysis, namely data collection, data reduction, data display, and drawing conclusions. The results showed that (1) the school principal planned to increase the professionalism of teachers based on religious culture including planning based on the Strategic Plan, vision, mission, school goals, and needs, involving all school members, recruiting new teachers. (2) Providing guidance through involving teachers in scientific forums, further studies, revitalizing MGMP, establishing teacher silaturrahim forums, and adding supporting facilities. (3) Evaluation through individual or group supervision both directly and indirectly on aspects of teacher attendance assessment, teacher performance in schools, and student development.